2018
DOI: 10.1186/s12886-018-0921-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic memory in mitochondrial oxidative damage triggers diabetic retinopathy

Abstract: BackgroundDiabetic retinopathy (DR) is a microvascular complication induced by high blood glucose. This study was conducted to investigate the effect of metabolic memory on mitochondrial oxidative damage-induced DR.MethodsRat retinal endothelial cells (rRECs) were isolated from SD rats and treated with high glucose (20 mM) for various times and then cultured in normal glucose (5.6 mM) medium for 2 days. The cells were assayed for the expression of respiratory chain complexes cytochrome c oxidase subunit 1 (CO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…A growing body of experimental evidence supports the concept that the risk for diabetes complications may be linked to oxidative stress, non-enzymatic glycation of proteins, epigenetic changes, and chronic inflammation, laying the foundation for the MM theory 30. Nigris et al reported that dipeptidyl peptidase-4 (DPP-4) induced oxidative stress in the HUVECs and MM in retinal endothelial cells,31,32,33 which could be reduced by the inhibitor teneligliptin32,33 We analyzed the protein-coding mRNA expression profile by high throughput RNA-seq in HUVECs from the LG, HG, and MM groups. HGMMGs were identified, including 516 up-HGMMGs and 210 down-HGMMGs.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of experimental evidence supports the concept that the risk for diabetes complications may be linked to oxidative stress, non-enzymatic glycation of proteins, epigenetic changes, and chronic inflammation, laying the foundation for the MM theory 30. Nigris et al reported that dipeptidyl peptidase-4 (DPP-4) induced oxidative stress in the HUVECs and MM in retinal endothelial cells,31,32,33 which could be reduced by the inhibitor teneligliptin32,33 We analyzed the protein-coding mRNA expression profile by high throughput RNA-seq in HUVECs from the LG, HG, and MM groups. HGMMGs were identified, including 516 up-HGMMGs and 210 down-HGMMGs.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial ETC is a major source of ROS induced by vascular endothelial growth factor (VEGF) in hyperglycemic and hypoxic cellular environments ( Cheng et al., 2011 ; Pearlstein et al., 2002 ; Wang et al., 2018 ). In PDR, increased mitochondrial ROS and impaired Ca 2+ signaling can cause an increase in oxidative stress ( Kowluru and Mishra, 2015 ; Pangare and Makino, 2012 ; Tang et al., 2014 ; Wang et al., 2018 ). Complex III of the ETC was recently shown to be important for umbilical vein EC respiration and thus proliferation during angiogenesis ( Diebold et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial electron transport chain (ETC) is a major source of ROS induced by vascular endothelial growth factor (VEGF) in hyperglycemic and hypoxic cellular environments (Cheng et al, 2011;Pearlstein et al, 2002;Wang et al, 2018). In PDR, increased mitochondrial ROS and impaired Ca 2+ signaling can cause an increase in oxidative stress (Kowluru and Mishra, 2015;Pangare and Makino, 2012;Tang et al, 2014;Wang et al, 2018). Complex III of the ETC was recently shown to be important for umbilical vein EC respiration and thus proliferation during angiogenesis (Diebold et al, 2019).…”
Section: Discussionmentioning
confidence: 99%